Consensus between users and preparers on the importance of voluntary disclosure items in annual reports : an Indonesian study / Arifin Sabeni, Hasnah Haran and Daing Nasir Ibrahim - Sabeni, Arifin; Haran, Hasnah; Ibrahim, Daing Nasir (Faculty & Accountancy & Accounting Research Institute (ARI), 2002)
This study examines the perception of users (stockbrokers, investment managers and underwriters) and preparers (managers of public-listed companies) in.Jndonesia regarding the importance ofvoluntary disclosure items that appearin annual reports ofIndonesian public-listed companies. A questionnaire containing 58 voluntary items was sent to both users andpreparers. An analysis ofthe results show that out ofthe 58 voluntary items, users perceived 24 items as 'important' to 'very-important', while preparers only perceived 12 items to be so. The level ofconsensus among groups of users is high, while the level of consensus between groups of preparers is considered moderate (65.52%). It is also found that there are 19 voluntary items categorized as 'important' to 'very important' perceived by both users andpreparers and the level ofconsensus between users and preparers is equal to 70.69%. It is thus suggested that these 19 items should be made mandatory and be included as part ofthe annual reports.